The Development of a Management for The Prevention of Non - Communicable Diseases in Preschool Children Risk Group Among Care Giver Through Community Participation in Warinchumrab District, Ubonratchathani Province - Feangphong, Natanong; Thienphuridej, Thamakorn (Journal of The Royal Thai Army Nurses, 2023)
The objective of this action research was to develop guidelines for the prevention of non-communicable diseases in preschool children risk group among care giver through community. The target group consisted of 24 care giver children in the non-communicable diseases risk group, six village health volunteers and two officials from Health Promoting Hospital. The situation analysis. The tools used in this research interviews, in-depth interview and discussion group guidelines and the record of the observation of the participation in the activities. Content analysis was employed to analyze qualitative data and descriptive statistics were used to analyze quantitative data. The study results revealed: 1. The situation analysis of the risk of preschool care giver children group included low knowledge of non-communicable diseases in preschool children and self-efficacy and inappropriate health care behavior. 2. The brainstorming meeting was held for planning development of practice guideline for prevention of non-communicable diseases preschool children risk group among care giver through community participation. The guideline was as follows: 1) improve knowledge of non-communicable diseases, 2) improve self-efficacy, 3) organize activities to improve health care behaviors, 4) having home visits and follow-up through the social network 3. The result after the development: the risk of preschool care giver children group, s knowledge, self-efficacy and health care behaviors were increased significantly (p < .05). An effective model for the prevention of non-communicable diseases preschool children risk group among care giver in community was developed.